In-service training policy during the COVID-19 pandemic: The case of the agents of the farmers, rural people, and nomads social insurance fund - Ghadermarzi, Hamed; Ataei, Pouria; Mottaghi Dastenaei, Afshin; Bassullu, Caglar (Frontiers in Public Health, 2023)
The COVID-19 pandemic has posed the in-service training of agents of the Farmers, Rural People, Nomads Social Insurance Fund (hereafter the Fund) to many problems. In-service training is one of the most effective development factors for organizational goals. This sort of training will increase employees’ skills and subsequently improve their job performance. Accordingly, the present research mainly aimed to shed light on the effect of in-service training policy on employees’ capabilities and job performance. The research was conducted among the agents of the Fund in Fars province, Iran (N = 197) out of whom 127 agents were sampled by simple randomization. The research instrument was a standard questionnaire whose face and content validity was confirmed by a panel of experts and its reliability was determined by calculating Cronbach’s alpha in a pilot study. The results showed that the indicators used to measure the research variables were acceptably consistent with the factor structure and the theoretical framework of the research. Based on the findings, in-service training in the Fund during the COVID‑19 pandemic has had a positive and significant effect on the agents’ capabilities (communication and team-working skills, creativity and problem-solving skills, commitment and responsibility, technical information and knowledge, and technical and practical skills) and job performance at the individual, technical, and general levels. Also, the agents’ capabilities have had a positive and significant influence on their job performance. It can be concluded that in-service training can influence the agents’ capabilities and job performance and improve organizational performance during the COVID‑19 pandemic. Thus, the enhancement of in-service training courses’ quantity and quality during the COVID-19 pandemic can influence the job performance of the agents at the individual, general, and technical performance levels.